Adaptive sports medicine in the para-athlete - Fisher, M. (2021)
Objectives • Define Adaptive Sports Medicine and the Paralympic movement • Describe the pre-participation exam for the para-athlete • Review the benefits of physical activity and sport for individuals with disability • Review common medical considerations of physical activity in those with congenital and acquired disability